Restock management system by using market basket analysis / Nazrin Adnan - Adnan, Nazrin (2016)
Malaysians’ retail store especially huge company or store nowadays mostly used system technology in order to make sales run smoothly and more faster. The problem occurs when small retail store notably for new company have a desire to use the system in order to maintaining performance and market for the product. Small retail store sometimes hire employee to check and restock item when it was almost out of stock. Besides that, certain small retail store that have no other employees apart from owner forgot to check the item periodically and forgot to restock if necessary. System is very useful of any area for enhance the capability of the works. The purpose of this paper is to provide a system for small retails store that have small budget but needs to use system for survive their sales. This study is focus on Market Basket Analysis which is analyze the customer purchase behavior from previous purchases by using apriori algorithm. Market Basket Analysis will analyze the frequent itemset that has been brought by customer while apriori algorithm will learn step by step each of the item through the purchases history. This Market Basket Analysis come out with their own criteria and give suggestion and also prediction of item that need to be alert for next restock. The criteria used for the algorithm is previous of customer purchase. To achieve this requirements, a Visual Basic 6 language is used for develop this system as platform and MSAcess Databse use for save and retieve data for analysze purpose. This system not only provide for small retails store but is also can be used for huge company. The research provides a basis for enhancing and developing for more effective system as well as provide reliable system to positively influence owners’ future sales.